The effect of eight weeks aerobic exercise on psychological symptoms of premenstrual syndrome - Zahra Mohebbi-Dehnavi; Farzaneh Jaafarnejad; Zahra Kamali; Ala-Saber Mohammad (Tehran University of Medical Sciences, 2017)
Background & Aim: Premenstrual syndrome includes physical and psychological symptoms that occur at the end of menstrual cycle and exercise is one of the ways to reduce symptoms. The aim of this study was to determine the effect of regular 8-week aerobic exercise program on psychological symptoms of premenstrual syndrome. Methods & Materials: This clinical trial study was carried out on 65 dormitory students of Mashhad University of Medical Sciences. The samples were selected using available sampling method and were included in the study if they had premenstrual syndrome. The intervention group performed aerobic exercise for 8 weeks, three times a week and 20 minutes for each session. The control group completed only the questionnaires. The tool was research recorded daily symptoms of premenstrual syndrome. Data analysis was done using SPSS software. Results: At the beginning of the study, two groups of control and intervention were homogeneous for demographic variables and psychological symptoms. According to the results of independent t-test, the scores showed after intervention, Among the ten psychological signs of premenstrual syndrome, four signs of anger outbreak (p = 0/01), loneliness (p = 0.04) and irritability (p = 0/01), Mood swings (p = 0.01) difference Has a significant relation with the control group, However, the difference in pre and post scores in the two groups was significant only in the symptom of mood fluctuation (p = 0.02). Conclusion: The results of this study showed that eight weeks of aerobic exercise training were effective in reducing the number of psychological symptoms of premenstrual syndrome, Therefore, these exercises may be combined with other therapies for the treatment of psychological symptoms of premenstrual syndrome.